PERNIKAHAN BEDA AGAMA DALAM PERSPEKTIF HUKUM ISLAM DAN ASAS KEPASTIAN HUKUM: (STUDI KASUS DI KOTA TOLERANSI SE-INDONESIA) - ASEP SARIP HIDAYATULLAH ASEP (SAMAWA, 2025)
Interfaith marriage is a complex issue in Indonesia’s religious and multicultural society. In Islamic law, marriage between a Muslim—especially a Muslim woman—and a non-Muslim is strictly prohibited, as outlined in QS. Al-Baqarah verse 221 and Articles 40 and 44 of the Compilation of Islamic Law. However, Law No. 1 of 1974 does not explicitly prohibit it, as long as it is conducted according to each religion’s legal provisions. Salatiga, known as the city with the highest tolerance index in Indonesia, serves as a unique case study for this phenomenon. This research applies a qualitative case study method. The analysis is based on maqashid al-shari‘ah to examine Islamic normative dimensions and Hans Kelsen’s legal certainty theory to evaluate the national legal framework. The findings show that interfaith marriages in Salatiga are carried out through various means such as marrying abroad, temporary religious conversion, or court applications. These practices reveal the lack of legal certainty in Indonesia’s marriage law, and the ongoing tension between religious norms and individual freedoms. This article highlights the need for regulatory reform to uphold both public welfare (maslahah) and legal certainty. Keywords: interfaith marriage, Islamic law, maqashid al-shari‘ah, legal certainty, Salatiga.